2021
DOI: 10.1038/s41394-020-00356-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and spinal cord injury and disease: results of an international survey as the pandemic progresses

Abstract: Study design An online survey. Objectives To follow-up with and re-query the international spinal cord community's response to the Coronavirus Disease 2019 (COVID-19) pandemic by revisiting questions posed in a previous survey and investigating new lines of inquiry. Setting An international collaboration of authors and participants. Methods Two identical surveys (one in English and one in Spanish) were distributed via the internet. Responses from both surveys were pooled and analyzed for demographic and respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 11 publications
0
44
0
Order By: Relevance
“…Regardless, as research has confirmed that poor access to health services during the pandemic can contribute to increased secondary health issues for people with SCI, it is possible that the referenced conditions were a result of being unable to receive allied health and specialist support. For example, a survey of rehabilitation clinicians confirmed that during the pandemic clients with SCI had limited access to essential health services, and experienced increased medical complications (Gustafson et al, 2021 ). Furthermore, cross‐sectional work eliciting the opinions of people with SCI during the pandemic has confirmed poor access to health services and increased secondary complications as concerns (Hearn et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, as research has confirmed that poor access to health services during the pandemic can contribute to increased secondary health issues for people with SCI, it is possible that the referenced conditions were a result of being unable to receive allied health and specialist support. For example, a survey of rehabilitation clinicians confirmed that during the pandemic clients with SCI had limited access to essential health services, and experienced increased medical complications (Gustafson et al, 2021 ). Furthermore, cross‐sectional work eliciting the opinions of people with SCI during the pandemic has confirmed poor access to health services and increased secondary complications as concerns (Hearn et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased spasticity (10.3%) and rigour (6.9%) were also reported as atypical presentations of COVID-19. Similarly, Gustafson et al [ 35 ] conducted another online international survey from May 21, 2020 to June 10, 2020, to assess the health care professionals’ experiences, knowledge and concerns of the COVID-19 pandemic SCI. Three hundred and sixty-six professionals (among them 63.1% were rehabilitation physicians) participated.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 366 professionals, only 12.1% responded that they had patients with SCI with COVID-19 infection. In this review [ 35 ], the most frequently cited presenting symptoms were fever (7.9%), shortness of breath (6.8%), sweats (1.6%), increased spasticity (1.6%), increased pain (1.4%), rash/peripheral lesions (1.4%) and anosmia (1.1%). In both surveys [ 34 , 35 ]), the cough was not reported as a common presenting feature of COVID pneumonia in SCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a fear of having to attend hospitals, but non-attendance could lead to greater complications of untreated conditions. Attempts to address some of these issues include the increased use of telehealth to reduce the need for in-person appointments with doctors and physical therapists ( 9 ).…”
Section: Introductionmentioning
confidence: 99%